Violencia estructural, ejercicio de análisis de la realidad de comunidades indígenas Wichí, Quom y Pilagá en la provincia argentina de Formosa - Böhm, María Laura (2017)
In the present paper the concept of structural violence of Johan Galtung and his analytical potential is explained. It is applied here to the study of communities and localities Wichí, Qom and Pilagá of the Argentine province of Formosa. The analysis makes visible the marginality in which these communities live, but at the same time emphasizes that it is not possible to make a binary proposal as to the satisfaction or dissatisfaction of basic needs, and therefore of structural violence. It is argued that it is necessary to introduce the variable time and the possibility of graduality in the evaluation of reality. In this way, the description, analysis and criticism on the one hand, and the design of intervention programs, on the other hand, would fit to the specific contexts of reality, and not only to guidelines of general theoretical discourse.